PERAN KOMITMEN DALAM MEMEDIASI PENGARUH PELATIHAN TERHADAP KINERJA GURU DI SD AL-ULUM ISLAMIC SCHOOL KOTA PEKANBARU - ,Dewita Suryati Ningsih, Alif Alvi Nanda , Sri Indarti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the role of commitment in mediating the effect of training on teacher performance at Al-Ulum Islamic School Elementary School which is located on Jl. Tuanku Tambusai, Pekanbaru, Riau. The population in this study included all teachers at SD Al-Ulum Islamic School, totaling 36 people. Primary data were collected by using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using SmartPLS 3.0 analysis. The sampling technique that has been chosen is the census method (36 people at SD Al-Ulum Islamic School). The results showed that: 1) There was a significant effect of training on teacher performance at SD Al-Ulum Islamic School Pekanbaru City, 2) There was a significant effect of training on commitment at SD Al-Ulum Islamic School Pekanbaru City, 3) There was a significant effect of commitment on significant effect on teacher performance at SD Al-Ulum Islamic School Pekanbaru City, 4) There is a significant effect of training on teacher performance through commitment as a mediating variable at SD Al-Ulum Islamic School Pekanbaru City. Keywords: Performance, Training and Commitment